Branding Through Influencer Marketing on Instagram - Phamová, Giang Helen (2020)
This bachelor thesis analyses branding on Instagram with a focus on Influencer marketing. The purpose of this thesis is to explore how influencer marketing can help to increase brand awareness. The first part of this thesis describes the analyzed platform, Instagram. The next part of the thesis focuses on Influencer marketing, influencers and collaborations with them. The last chapter is dedicated to case studies that present three brands' collaborations with influencers in order to increase brand's awareness on Instagram.